Declines in social–emotional skills in college students during the COVID-19 pandemic - Cerutti, Janine; Burt, Keith B.; Moeller, Robert W.; Seehuus, Martin (Frontiers in Psychology, 2024)
The present study investigated whether social-emotional skills in first year college students differed before and after the coronavirus disease (COVID-19) lockdowns. Participants (N = 1,685) consisted of first year college students (mean age 18.53 years) selected from a broader cohort enrolled in a longitudinal study on college mental health at liberal arts colleges in the United States. In a cohortsequential design, participants completed an online survey assessing social-emotional skills in January of 2018, 2019, 2020, and 2022. Using analysis of covariance, we examined mean differences in social-emotional skills between students who were first years before (January 2018-2020) and after the lockdowns (January 2022), controlling for sociodemographic variables. The post-lockdown group scored significantly lower on emotional control and expressivity and marginally higher on social sensitivity compared to the pre-lockdown group. No group differences in social/emotional expressivity or social control were detected. These findings indicate that the COVID-19 lockdowns impaired some, but not all, social-emotional skills in first year college students. Addressing socialemotional skills in college may help to reduce the COVID-19 mental health burden.